2009
DOI: 10.1021/jo802723w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Macrocyclic β-Strand Templates by Ring Closing Metathesis

Abstract: We report the synthesis of macrocycles 1-6 via ring closing metathesis of dienes 7-12. Addition of chlorodicyclohexylborane to thermal and microwave assisted RCM of dienes 8 and 9 markedly improves the yield. The geometric isomers of macrocycles 1-3 and 5 have been assigned using X-ray crystallography and NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…24 In this study the geometry of a related sequence was confirmed by X-ray crystallography. 24 For both of these peptides a single alkene isomer was obtained which was assigned the ( E )-configuration based on the alkene coupling constant 27 (15.8 Hz for 7 ). The C-terminal ferrocenyl group and N -terminal free amine were introduced as above.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…24 In this study the geometry of a related sequence was confirmed by X-ray crystallography. 24 For both of these peptides a single alkene isomer was obtained which was assigned the ( E )-configuration based on the alkene coupling constant 27 (15.8 Hz for 7 ). The C-terminal ferrocenyl group and N -terminal free amine were introduced as above.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, an X-ray crystallographic analysis of (10), an intermediate in the synthesis of (9b) (see ORTEP [249] diagram in Fig. (9)), shows the desired extended -strand conformation for the macrocycle [250]. The 17-membered peptide aldehyde (9b) is particularly active (IC 50 = 30 nM) towards calpain 2, with greater than 7-fold selectivity for this isoform.…”
Section: Peptide Aldehydesmentioning
confidence: 99%
“…(9). ORTEP [249] diagram of the X-ray crystal structure of the peptide macrocycle (10), an intermediate in the synthesis of (9b) [250]. cellular calpain assays with IC 50 values in the low micromolar range [255].…”
Section: Peptide Hemiacetals (Aldehyde Prodrugs)mentioning
confidence: 99%
“…113 Abell et al demonstrated the ring closing metathesis approach in the synthesis of S-containing bridged benzannulated macrocycle 189 (E/Z ratio: 11 : 1) from scaffold 188 using MW irradiation combined with Lewis acid conditions (Scheme 6h). 114 Ring-closing metathesis (RCM) has been extensively used for the synthesis of resorcylic acid lactones (RALs). 115 There are numerous parameters that inuence metathesis reactions; therefore, there are no general conditions that can be given that will guarantee the success of the process.…”
Section: Ring-closing Metathesis (Rcm)mentioning
confidence: 99%